Bacterial contamination of chicken meat in slaughterhouses and the associated risk factors: A nationwide study in Thailand. - Kunnanut Klaharn; Duangporn Pichpol; Tongkorn Meeyam; Thanida Harintharanon; Patpong Lohaanukul; Veerasak Punyapornwithaya (PLoS ONE, 2022)
Slaughterhouses are a key source of bacterial contamination in poultry meat and products, which is a major health and economic concern for several public authorities. This study aimed to quantify the non-compliance of bacterial contamination on chicken meat sampled from slaughterhouses and identify risk factors associated with the contamination. A questionnaire survey of 569 chicken slaughterhouses was undertaken and 1,707 meat samples were collected to determine the level of bacterial contamination. The proportion of the non-compliance associated with aerobic plate count [APC] (24.6%), Staphylococcus aureus (6.3%), Enterococcus spp. (24.7%), coliforms (13.5%), Escherichia coli (33.3%), and Salmonella spp. (33.4%) based on the livestock authorities' criteria was determined. Our results highlighted that the scalding process without scalding water temperature control or improper scalding increased the risk of APC (odds ratio, OR = 4.84, 95% CI: 2.72-8.61), S. aureus (OR = 2.68, 95% CI: 1.29-5.55), Enterococcus spp. (OR = 3.38, 95% CI: 2.01-5.69), coliforms (OR = 3.01, 95% CI: 1.47-6.15), and E. coli (OR = 2.69, 95% CI: 1.58-4.56) contamination on meat samples. Meat from eviscerated carcasses was more likely to be non-compliance due to contamination by E. coli (OR = 1.96, 95% CI: 1.14-3.38). Furthermore, open or semi-closed system slaughterhouses (OR = 1.79, 95% CI: 1.23-2.60) and lack of equipment for specific slaughtering areas (OR = 1.65, 95% CI: 1.04-2.61) increased the likelihood of Salmonella spp. occurrence. This is the first study of factors influencing the non-compliance of meat samples across Thailand. Authorities can use the study findings to enhance food safety strategies at the national level.